Keberlanjutan Program Pertanian Keluarga dalam Masa Pandemi Covid-19 di Kabupaten Kepulauan Tanimbar - Nancy Slarwamin; Agnes Pudjiastuti; Sumarno Sumarno (Jurnal Sosial Ekonomi Pertanian, 2021)
Covid-19 pandemic has a negative impact on agricultural sector and threatens various aspects of life. Family farming program is one of the government's efforts to protect farmers and improve the welfare of farmer families. The study aims to analyze the sustainability of family farming program in the Tanimbar Islands Regency according to ecological, social and economic aspects, and the most influential dimensions. The research was conducted in Adaut Village and Amdasa Village, Tanimbar Islands Regency because these two villages were the program implementation locations. Data were collected from all farmers participating in the family farming program. Data were analyzed by multidimensional scaling with Rapfish to see the sustainability status of the program and its most influential dimensions. The results showed that the family farming program was not sustainable in the Tanimbar Islands Regency. This program has been implemented relatively recently in this area. The dimensions that were most influential differed between the two villages. There needs to be a re-evaluation of the sustainability program periodically.